Herramientas espaciales para la mejora de la gestión de la información en alerta sanitaria por COVID-19 - Zúñiga Antón, María; Pueyo Campos, Angel; Postigo Vidal, Raúl (Geographicalia, 2020)
The Group of Studies on Spatial Planning (GEOT) of the Department of Geography of the University of Zaragoza, in collaboration with the City Council of Zaragoza and the Geographic Institute of Aragon, has been working since June 2020 on the research project entitled: "Development of geospatial support tools for improving the management of information on health alerts in the COVID-19 and its epidemiological, social and economic governance". The general objective of the project is to offer working protocols that integrate the massive treatment of social, economic and health information. Data will be used for its subsequent analysis and multiscale representation through thematic mapping. It will serve as a basis for the development of health, social and economic policies to mitigate / eliminate the effects of COVID-19.Translated with www.DeepL.com/Translator (free version)